EFFECTIVENESS OF CHROMATOGRAPHIC METHOD FOR ORDERING SECONDARY METABOLITE COMPOUNDS ON PLANT (PEPEROMIA PELLUCIDA L.) WITH METHANOL SOLUTIONS - Lutfiana Kartika Dewi; Muhammad Ghufron; Ngain Kristin (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to determine the effectiveness of chromatographic methods to isolate secondary metabolite compounds in methanol condensed extracts of surrogate plants. A total of 200 grams of simplified planting plants were macerated with methanol solvent for 8x24 hours. The resulting maserate is further distilled to produce a methanol condensed extract of 40 grams. Methanol condensed extract was further analyzed by using thin layer chromatography to see how many compounds in the sample. The result of the thin chromatography obtained by the color of the basket showing in the plants there are somecompounds. Keywords: Surety, Isolation, Simplicia, Secondary Metabolite, Flavonoids